Spatial Structure of Mountain Forests of the Lake Baikal Southwestern Coast (Global Journal of Human-Social Science, 2017)
Spatial structure of mountain forests of the Baikal region is presented through geobotanical mapping. Correlated analysis of the vegetation cover structure and data of landscape investigations was done. The study area is characterized by a high natural diversity of plant communities with dominating forests reflecting the ecotopes differentiation in mountain conditions as well as by the contact of regional physical geographical structures and experiencing anthropogenic impacts. The map legend conveys the identified spectrum of forests diversity. Area is provided for the integrated stability areas of plant communities. Forest stability is regarded as ability of plant communities to retain their phytocenotic structure. An expert assessment of stability is made. This territory is notable for dominance of stable and moderately stable forest communities. The modern mosaic-dispersed distribution of communities of equifinal successional stages gives evidence of the current favorable conditions for preservation of dark coniferous forests.
Keywords: forests spatial structure; mapping; landscape structure; forests stability